P102 The liverpool healthy lung project – seeking out early stage lung cancer. (15th November 2016) - Ledson, MJ; Grundy, S; Gaynor, E; Arvanitis, R; Timoney, M; Field, J
Abstract : Liverpool has one of the highest respiratory morbidity rates in England, with double the lung cancer incidence, particularly in lower socioeconomic groups. To tackle this health inequality in February 2016 in conjunction with Liverpool CCG, the primary care sector, public health and Liverpool University we commenced the 3-year £3.3M Liverpool Healthy Lung Project. The project has 2 sequential phases. Phase 1: By means of a series of coordinated focused public engagement events throughout the city, starting in areas with higher lung cancer incidence, this aims to promote positive messages around lung health, and address the fear and fatalism surrounding lung cancer. Phase 2: All individuals between the ages of 58–70 who have COPD, have smoked, or are asbestos exposed are invited to a face to face lung health check conducted by an experienced respiratory nurse. Positive lifestyle messages are promoted and a 5-year personal lung cancer risk calculated (www.MyLungRisk.org using LLPv2 risk model). Those who trigger the 5% threshold are offered a low dose thoracic CT scan. The community healthy lung events attracted 1346 interactions and 462 individuals completed spirometry. 90 (19%) of these tests were abnormal which triggered a consultation in primary care. Projections suggest 34, 000 patients will be eligible for phase 2: in the first 12 weeks, in Picton Ward (eligible population 2471) 896 (36%) individuals booked to attend the lung health check, where 230 (31%) triggered the offer of a CT. To date 138 scans have been reported: 24 (17%), had significant findings, of which 9 (6%) require a 3 month and 3 (2%) 12 month repeat scan for nodules. Two individuals had confirmed cancer (both resected), with 2 further cases currently being worked up. Of 406 patients (45%) without previously diagnosed COPD, 180 (44%) had abnormal spirometry, and have gone on to further diagnostics. The complete Picton Ward data will be presented at the conference. This innovative project is already improving access to respiratory healthcare in a deprived area of Liverpool, and should improve outcomes for lung cancer in this disadvantaged population. The project has been adopted by the national ACE program.